Akar Tradisi Toleransi di Indonesia dalam Perspektif Peradaban Islam - Kusmana Kusmana (JURNAL INDO-ISLAMIKA, 2017)
This paper delves chronologically the root of Indonesian Muslims’ tolerance tradition in the history of Islamic civilization starting from the period of caliphate to the modern one to cherish this tradition in the country. Here, this study uses a descriptive and analytical method to problematize how Muslims in Indonesia gratify themselves with the tradition of tolerance from the Islamic civilization history they read to resolve intolerance that has recently emerged. This study uncovers that Muslims in Indonesia have actually learned that the Islamic civilization history depicts the tolerance tradition concepts prior to this convention in the West. This paper argues that this understanding is potential to be a social capital for Muslims in Indonesia to cultivate the tolerance tradition in the country; thereby being able to perpetuate Islam as the religion of ‘blessing for all universe’ (rahmatan li-al‘alamin).